Succinate receptor (version 2019.4) in the IUPHAR/BPS Guide to Pharmacology Database (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
Nomenclature as recommended by NC-IUPHAR [7]. The Succinate receptor has been identified as being activated by physiological levels of the Kreb's cycle intermediate succinate and other dicarboxylic acids such as maleate in 2004. Since its pairing with its endogenous ligand, the receptor has been the focus of intensive research and its role has been evidenced in various (patho)physiological processes such as regulation of renin production, retinal angiogenesis, inflammation or immune response.